The impact of ecotourism on community’s livelihood: A study on local community in Kadamaian, Sabah - Noor Fzlinda Fabeil; Marry Tracy Pawan; Awangku Hassanal Bahar Pengiran Bagul; Kamarul Mizal Marzuki; Mori Kogid; Yuzainy Janin (Faculty of Business, Economics and Accountancy, 2021)
Tourism has been an important alternative strategy for rural development through improving the economies and societies of the rural people. Nevertheless, there is a dearth of study on the impact of tourism development on community’s involvement and their livelihood. This paper explores from the local community’s point of view how tourism contributes as a new livelihood, in terms of changes in household income. Face-to-face structured interviews with 12 local communities from 6 ecotourism sites in Kadamaian, Sabah revealed that the economic status of the local communities interviewed are mainly ‘below than average’ that their income level is below the National Poverty Line Income (PLI). Two-thirds of them agreed there is an increase in their household income after joining the ecotourism-related business, mainly as small business owners, and some are part-time workers or helpers at the ecotourism sites. The findings also found that although respondent perceived ecotourism as important for livelihood, they are still ambivalent that tourism can alleviate poverty, which mainly caused by a lack of entrepreneurial skill. This study lends insights to ecotourism operator and policymakers to provide the local community with relevant capacity building and to ensure total support from other actors in the ecotourism supply chain, like NGOs, universities, volunteers, government, in line with the trickle-down concept of tourism i.e. tourism-led growth strategy (TLG).